1459 Intravesical Chemohyperthermia Versus Bacillus Calmette-Guerin Instillation for Intermediate- And High-Risk Non-Muscle Invasive Bladder Cancer: A Systematic Review and Meta-Analysis. (12th October 2021) - Zhao, H; Chan, V W S; Castellani, D; Chan, E O T; Ong, W L K; Peng, Q; Moschini, M; Krajewski, W; Pradere, B; Ng, C F; Enikeev, D; Vasdev, N; et al.
Abstract: Introduction: Traditional intravesical chemotherapy instillations under room temperature post trans-urethral resection (TUR) of non-muscle invasive bladder cancer (NMIBC) have lower efficacies than maintenance BCG installations. Intravesical chemo-hyperthermia (CHT) at higher temperatures is developed to improve the efficacy of chemotherapy instillation. This systematic review aims to compare the use of CHT and BCG instillation post-TUR. Method: The protocol of this review is registered on PROSPERO(CRD42020223277). A comprehensive literature search was performed on Medline, EMBASE, and Cochrane CENTRAL to identify studies comparing CHT and BCG post-TUR for intermediate- or high-risk NMIBC. Primary outcomes include recurrence-free survival (RFS) and progression-free survival (PFS). Secondary outcomes include adverse events (AE). Results: From 2, 375 identified records, four randomised control trials incorporating 327 patients were included for meta-analysis. The use of CHT was found to be non-inferior to BCG in RFS, PFS and AEs (Grades 1-3) (p > 0.05). Sensitivity analysis, excluding patients with BCG failures, show 24-36 months recurrence rate to be significantly lower in CHT group (RR 0.64, 95% CI 0.42-0.98, p = 0.04) compared to the BCG group. In patients without carcinoma in situ (CIS), RFS is also significantly better in CHT patients (HR 0.52, 95% CI 0.32- 0.85, p < 0.01). Safety profile remains non-inferior to the BCG group in sensitivity analyses. Quality of evidence across all outcomes ranged from moderate to low. Conclusions: In well-selected patients, intravesical CHT has superior oncological outcomes and non-inferior safety profile when compared to BCG maintenance therapy for patients with intermediate- and high-risk NMIBC. CHT is a possible alternative treatment during BCG shortage.